Formation mechanism of electrical discharge TiC-Fe composite coatings - Murray, J.W.; Algodi, Samer J.; Fay, Mike W.; Brown, Paul D.; Clare, Adam T. (Elsevier, 2016)
Comparison of electric discharge (ED) processed single deposit and continuum TiC-Fe cermet coatings, formed from a sacrificial powder metallurgy TiC tool electrode at negative polarity, on 304 stainless steel, provided insight into the ED coating (EDC) formation mechanism. A deposit from a single spark event was dominated by TiC, phase separated from a ∼2 wt% Fe matrix, with strongly aligned grains and banded microstructure, indicative of solidification from the coating/substrate interface. Conversely, a continuum coating, subjected to ∼200 spark events per location, exhibited a more complex, banded microstructure, with a mixture of equiaxed and columnar TiC grains within a ∼30 wt% Fe-based matrix, along with some concentrations of carbon from the oil dielectric. It is considered that each sparking event remelts previously solidified coating material, with or without further TiC particle incorporation, leading to gradual TiC dilution and the development of a TiC-Fe composite coating with increasing levels of substrate material forming the matrix.